Corak Sistim Peternakan Berbasis Sosio-Ecofarm di Distrik Bruyadori, Biak Numfor-Papua - Deny Anjelus Iyai (State Islamic University (UIN) Alauddin, 2021)
The purpose of this study was to determine the portrait of livestock production in the neighborhood environment as a basis for livestock commodity development and animal husbandry development, to determine the needs and potential of animal husbandry development in Biak-Numfor Regency. The method in this research is descriptive survey technique. The sample of respondents selected as many as 30 heads of families who do livestock raising work in the village of Distrik Bruyadori. The object of observation is the socio-cultural aspects of the farmer, livestock production and perceptions and needs of livestock development. The findings showed that the socio-cultural portrait of farmers in the Distrik Bruyadori village was sufficient in terms of age (age) and experience, while the level of education needed to be pursued by attending training related to commodities. Livestock and animal pens need to be provided by the government with an alternative village fund program. Portrait of livestock production is not optimal, marked by the low number of livestock production per parent per birth of several commodities. Animal feed needs to be intensified. The business portrait is still not optimal because market access is not yet controlled by farmers. Thus technical assistance needs to be provided.